Effects of dietary creatine supplementation on kidney and striated skeletal muscles of rats submitted to ischemia and reperfusion of hind limbs - Moreira Neto,Antonio Augusto (2021)
ABSTRACT Purpose To evaluate the effect of creatine supplementation in the diet of rats subjected to ischemia and reperfusion of hind limbs. Methods Eighteen male Wistar rats were randomized to receive dietary creatine supplementation (G1) or no supplementation (G2), before being subjected to 4 h of ischemia followed by 4 h of reperfusion. In addition, 10 rats (G3) underwent the same surgical procedure, without ischemia, but with supplementation. After reperfusion, kidney and musculature were evaluated for histological damage and serum levels of alanine aminotransferase, urea and creatinine were obtained. Results The urea dosage showed significant differences between the groups (averages G1 = 155.1; G2 = 211.27; G3 = 160.42). Histological analysis found significant differences between G1 and G2 (but not between G1 and G3) in renal myoglobin cylinders and vacuolar degeneration variables and in hypereosinophilia and karyopyknosis variables in muscle fibers. There were no significant differences in the other variables studied. Conclusions Creatine supplementation was related to fewer histological lesions, as well as lower levels of plasma urea, which may suggest a protective effect against lesions caused by ischemia and reperfusion of posterior paws muscles in Wistar rats.